Construction and validation of a clinicopathologic signature for predicting the prognosis of stage II and III colorectal cancer - Weiqiang You (The Lancet Regional Health. Western Pacific)
Background: Various clinical and pathological indicators affect the prognosis of stage II and III colorectal cancer (CRC). Nevertheless, few studies have systematically integrated these indicators to construct a signature for assessing the prognostic risk. Methods: Patients with stage II-III CRC who underwent R0 radical resection from 2009 to 2016 were included in this study. All clinical and follow-up data were collected. Our study mainly incorporated an internal training cohort and an external validation cohort from two centers. Data processing and data analysis were performed in the R language. Cox proportional hazard regression was used for univariate and multivariable analyses. The log-rank test was performed to compare prognosis among groups. Findings: A total of 1200 eligible patients were included in our study. 8 variables, including T, N stage, lymphatic/vascular infiltration, preoperative CEA, CA125, and CA199, were included and the nomogram was established in the signature for predicting OS. The concordance index of the signature was 0.72. The 3-year and 5-year calibration curves of CRC based on the nomogram showed a perfect correlation between predicted and observed outcomes. Obvious differences were observed in the survival of different risk groups (p < 0.001). Patients with a low-risk score signature had a 5-year OS rate of 77%, whereas patients with a high-risk score signature had the worst 5-year OS rate (only 8%). Furthermore, our signature also achieved similar performance in external cohort validation. Interpretation: The signature based on clinical and pathologic factors had favorable accuracy for predicting the prognosis of stage II and III CRC. Therefore, our signature could identify high-risk patients with stage II and III CRC to guide adjuvant therapy and follow-up.